Affordability of Paediatric Oral Anti-Infective Medicines in a Selected District, Sri Lanka - Malith Kumarasinghe; Manuj C. Weerasinghe (MDPI AG, 2024)
In this cross-sectional descriptive study conducted in the Ratnapura district, Sri Lanka, we assessed the affordability of oral pediatric anti-infective medicines (OPAIMs). Using a modified WHO/HAI medicinal price methodology, we examined the availability, median price ratios (MPRs), mean percentage difference, and affordability of the standard treatment of the originator brand (OB) and lowest-priced generic (LPG) OPAIMs in 30 private and 2 state-owned pharmacies. The study revealed disparities in availability, with only 50% of private pharmacies offering all 11 medicinal drugs in their generic form. The MPRs of OPAIMs for OB and LPG varied, with three drugs exceeding the financially acceptable MPR of 2 (albendazole, amoxicillin, and erythromycin). The standard treatment with LPGs costs between 0.17 and 0.85 and between 0.06 and 0.28 days' wages for the lowest daily salary of the private sector and unskilled public employees, respectively. We identified erythromycin and albendazole as having less than 50% availability in their generic form in private pharmacies. To address these findings, we recommend frequent pricing revisions based on exchange rates and associated costs, coupled with the establishment of a transparent scientific criterion to subsidize essential medicines deemed "unaffordable." Failure to implement such measures amidst economic crises may adversely impact financial access to essential medications.